Optimizing fracture management: The role of the Ellis plate in distal radius fractures - Banna, Kiran Kumar; Minumala, Srikanth; Kannan, Dinesh; Badam, Swikrutha; Seela, Lakshminarayana (Asian Journal of Medical Sciences, 2024)
Background: Fractures at the distal end of the radius, a prevalent orthopedic concern, challenge clinicians due to their complex nature and the diverse patient demographics they affect. Primary stability is key, especially in cases involving osteoporotic bones or younger patients. The Ellis plate with a locking screw mechanism offers a promising solution to achieve this stability, potentially preventing secondary displacement regardless of bone quality. Aims and Objectives: This study aims to rigorously assess the effectiveness of the Ellis volar locking compression plate in treating distal end radius fractures. It focuses on evaluating functional outcomes post-treatment, providing insights into the efficacy of this approach. Materials and Methods: This study evaluated the efficacy of the Ellis plate in managing distal radius fractures, under ethical approval number KMC/IEC/Ortho/2021-5. Twenty adult patients with unstable fractures were included based on specific criteria and provided informed consent. Exclusion criteria included unwillingness for surgery, medical unsuitability, osteoporosis, minors, and compound fractures with vascular injury. Surgical outcomes were assessed using the Gartland and Werley scoring system, with follow-up appointments scheduled over 1 year to monitor progress and adherence to physiotherapy plans. Results: The study encompassed 20 patients, with a gender distribution of 12 males and eight females and an average age of 43.3 years. Utilizing the Gartland and Werley demerit grading system, the study reported 45% superb outcomes, another 45% good outcomes, 10% fair outcomes, and no poor outcomes. This distribution highlights the potential of the Ellis plate technique in achieving positive results in fracture treatment. Conclusion: The study concludes that the Ellis plate technique is a viable and effective option for stabilizing distal end radius fractures. However, achieving the best possible outcomes depends on several factors, including strict adherence to AO principles, maintaining high standards of aseptic practice, following appropriate post-operative rehabilitation protocols, and ensuring comprehensive patient education. This multifaceted approach is crucial for the successful treatment of these fractures.